1978
DOI: 10.1172/jci109131
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies on Segmental Sodium Transport in the Rat Kidney during Expansion of the Extracellular Fluid Volume

Abstract: A B S T R A C T The present studies were designed to further investigate the possibility of heterogeneity of nephron function during Ringer loading in the rat, and to determine the specific nephron segment responsible for this finding. As in previous studies from this laboratory with smaller rats (50-125 g), net addition of sodium between late distal tubule and papillary base (6.9 vs. 10.4% of the filtered load, respectively, P < 0.005) was found in more mature rats (170-230 g). In contrast, there was net reab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
0

Year Published

1982
1982
1987
1987

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 31 publications
3
22
0
Order By: Relevance
“…Earley and Friedler (3) suggested that renal vasodilatation may cause a natriuresis as a consequence of the washout of the hypertonic medullary interstitium occurring in this setting. Furthermore, recent studies from this laboratory have suggested that medullary washout may preferentially depress sodium reabsorption in the more inner cortical nephrons (4).…”
Section: Introductionmentioning
confidence: 99%
“…Earley and Friedler (3) suggested that renal vasodilatation may cause a natriuresis as a consequence of the washout of the hypertonic medullary interstitium occurring in this setting. Furthermore, recent studies from this laboratory have suggested that medullary washout may preferentially depress sodium reabsorption in the more inner cortical nephrons (4).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the FeNa of the superficial nephrons is affected by either procedure. In addition, these authors have demonstrated that after expansion with Ringer's solution the natriuretic response of the superficial nephrons is smaller than that of the nephrons located deep in the cortex (18,19). The results of our previous studies in young animals sustaining saline expansion (7) suggested to us that the observations of Osgood et al might be relevant to our understanding of the development of the natriuretic response to volume expansion.…”
Section: Discussionmentioning
confidence: 78%
“…Experiments performed by Osgood et al (18,19) have provided evidence that the expansion with Ringer's solution suppresses FeNa in the juxtamedullary nephrons,-whereas expansion with hyperoncotic albumin fails to do so. In contrast, the FeNa of the superficial nephrons is affected by either procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies (8) and those of others (9) have indicated that 10% body weight Ringer loading preferentially inhibits sodium reabsorption in juxtamedullary nephrons. More recently, we (10) suggested that this phenomenon was at least partially due to washout of the hypertonic medullary interstitium. Nevertheless, direct support for an important role of medullary tonicity in the control of urinary sodium excretion has been lacking.…”
Section: Introductionmentioning
confidence: 93%